A ética rizomática no Estado democrático de direito e o princípio da supremacia do interesse público - Ferreira, Dirce Nazaré de Andrade (2011)
This study wants to understand how ethics can approach the interpretation in neoconstitutionalism to implement the principle of supremacy of public interest law and update the board administrator making it approximately the Constitution. It was unethical state action by way of the supremacy of public interest from liberalism to the democratic rule of law. The trilogy State Constitution, and public management has been present in the modern state as the prospect of generating reasonable model that was able to rationally exclude the private interests of the public sphere. However, the State's intention remains blurred and unethical, as an abstract entity as the state is handled immediately by public officials that they embody the acts. Then the State by way of public interest and ethics departed immediately focused their public administrators. The reduction effected in this historic work has shown that since the phenomenon of the French Revolution of the State speech to drive out the private interest by way of public interest was paradoxical because acted by his managers and channeled efforts to the private interests of those who wield power . In this respect the constitution and the principle of the supremacy of public interest, were elements of rationality focused on the bourgeoisie. The rational aspects of the liberal state, as well as elements of the state's social welfare and the nuances of neoliberalism show how distorted the way in which the supremacy of public interest was channeled to the private will, devoid of ethics or using it so utilitarian. In the democratic state neoconstitutionalism questions the supremacy of public interest and unethical way the state set aside the citizen. Instead of strict administrative law, the Constitution is interpreted by mitigating the upright principles, trying to correct that distortion. Without ethics, this action becomes a new fallacy, because it represents new twist institutionally focused private interests, since the interpretation open can flow to focus the person subjectively and again the private interest. To support this complex relationship, ethics rhizomatic clings to the phenomenon from the perspective of interpreting the principle of supremacy of public interest through the constitutional principles and the principles of ethics as described by Gilles Deleuze's rhizome. Thus the law makes an interdisciplinary way with the sociology and philosophy by observing the principles: rupture, connection, multiplicity, cartography.